THE ROLE OF FEMINISM IN THE STRUGGLE FOR POLITICAL PARTICIPATION - Mancevska, Maja (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
This article explores the role of feminism in the struggle for equal participation of women and men in politics. Women make up half of the world’s population. Their participation in political life should reflect this and with political decisions being shared between genders. But the reality in the modern world shows that in politics, where power is concentrated, women are less represented particularly at top of the hierarchical structures. Feminism as a social movement has diminished gender "blindness" in politics, demanding equal rights for women and pushing for gender integration at almost all levels, up to the highest positions of power. If we make a review of the phases through which the creation of the social conditions for equal access of men and women to the key domains throughout history, especially in the European and Macedonian society, to the new concept of equal opportunities, one can conclude that it should have passed many centuries and patience, but above all persistence, until significant progress has been made, which is visible only in the last few decades. But even that "success" is not at a satisfactory level, nor at least not in practice.